The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/ncomms1436
|View full text |Cite
|
Sign up to set email alerts
|

Heterothermy in growing king penguins

Abstract: A drop in body temperature allows significant energy savings in endotherms, but facultative heterothermy is usually restricted to small animals. Here we report that king penguin chicks (Aptenodytes patagonicus), which are able to fast for up to 5 months in winter, undergo marked seasonal heterothermy during this period of general food scarcity and slow-down of growth. They also experience short-term heterothermy below 20 °C in the lower abdomen during the intense (re)feeding period in spring, induced by cold m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
0
33
2
Order By: Relevance
“…Even though those authors did not report a temperature for pectoral muscle, the fact that the thermal gradient between the deep core and the body shell can be as large as 8-15°C would indicate that pectoral muscles undergo a physiological hypothermia, at least similar to that measured in the thorax and the upper abdominal site near to the liver, i.e. down to 30-33°C (Eichhorn et al, 2011). Here, we show that such a level of heterothermy induced a significant 23% increase in the energy coupling efficiency at the level of mitochondria with an overall decrease in mitochondrial oxidative activity.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though those authors did not report a temperature for pectoral muscle, the fact that the thermal gradient between the deep core and the body shell can be as large as 8-15°C would indicate that pectoral muscles undergo a physiological hypothermia, at least similar to that measured in the thorax and the upper abdominal site near to the liver, i.e. down to 30-33°C (Eichhorn et al, 2011). Here, we show that such a level of heterothermy induced a significant 23% increase in the energy coupling efficiency at the level of mitochondria with an overall decrease in mitochondrial oxidative activity.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…Hence, changes in skeletal muscle mitochondrial efficiency would have no major impact on the intrinsic capacity of a chick's thermogenic mechanism during phase II of fasting. In conclusion, the regulation of the degree of mitochondrial coupling reported in fasted winter-acclimatized chicks triggers an economical management of resources at the level of mitochondria, which would, in association with short-term hypothermic stage, maximize the conservation of endogenous fuel stores and may contribute to the ability of king penguins to withstand fasting for several months (Cherel and Le Maho, 1985;Cherel et al, 1993a;Eichhorn et al, 2011). …”
mentioning
confidence: 99%
“…Such a decline in heart rate should indicate the presence of a developed dive reflex (including a vasomotor response; Butler and Jones, 1997). The strong decline in peripheral temperature observed in king penguin chicks during their winter fast also indicates the presence of an effective vasomotor control, months before they go to sea (Eichhorn et al, 2011).…”
Section: Potential Physiological Maturation Of the Thermoregulatory Rmentioning
confidence: 99%
“…During whole-body immersions in the laboratory, juvenile king and gentoo penguins (Pygoscelis papua) showed a gradual increase in internal insulation over time, suggesting that the peripheral vasoconstriction response was not fully developed upon first immersion (Barré and Roussel, 1986;Dumonteil et al, 1994). By contrast, Eichhorn et al (2011) reported a remarkable heterothermy in the body core and in peripheral tissues of free-living king penguin chicks throughout the winter period, when they fast for up to 5 months, in air (Cherel and Le Maho, 1985). Subcutaneous temperatures as low as 19°C and a temperature gradient between the core and the shell of up to 15.7°C were measured, indicating the presence of a peripheral vasoconstrictive response, long before their first departure to sea (Eichhorn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation